Up or Down? How Culture and Color Affect Judgments. (21st August 2013) - Jiang, Feng; Lu, Su; Yao, Xiang; Yue, Xiaodong; Au, Wing tung
ABSTRACT In the Mainland China stock market, an upmarket is represented by the color red, whereas a downmarket is represented by the color green. Elsewhere, including the Chinese Hong Kong stock market, the color representations are the opposite. Three studies were conducted to examine the red‐up–green‐down effect for Mainland Chinese as well as the green‐up–red‐down effect for Hong Kong people. Study 1 showed that Mainland Chinese tended to predict greater economic growth (study 1a) and higher growth in consumption trends (study 1b) when the experimental materials were presented in red than in green, whereas Hong Kong participants exhibited the opposite tendencies. Study 2 found that Mainland Chinese implicitly associated red and green with up and down, respectively; Hong Kong people, however, implicitly associated green and red with up and down, respectively. Study 3 further indicated that Mainland Chinese were more likely to predict good outcomes when scenarios were presented in red, whereas Hong Kong participants were more likely to predict good outcomes when scenarios were presented in green. These findings suggest that culturally specific environment cues could influence human prediction and judgment. Implications for judgment generally are discussed. Copyright © 2013 John Wiley & Sons, Ltd.